Valoración de la morbi-mortalidad mediante el sistema P-POSSUM de pacientes de Cirugía General en el Hospital Belén de Trujillo - Sachún Martínez, Karen del Rocío (2019)
OBJECTIVE: To establish the morbidity and mortality rate of General Surgery patients according to the P-POSSUM system at the Belén de Trujillo Hospital. MATERIAL AND METHOD: Descriptive, observational, longitudinal study. 254 medical records of patients treated at the General Surgery Service of the Belen de Trujillo Hospital, period December 2018 - February 2019, were analyzed. Morbidity and mortality were evaluated using the P-POSSUM system. RESULTS: The general average age was 42.59 years, 53.94% belonged to the female gender, with 76.77% of emergency surgeries, the most frequent admission diagnosis was acute appendicitis (34.18%) and the most frequent surgical procedure was appendectomy with 33.33% The main comorbidities present were high blood pressure (9.06%) and type 2 diabetes mellitus (3.54%). 72,835% presented high P-POSSUM-morbidity risk; and risk of low-moderate mortality in 36,614%. The evolution was torpid in 5.118%, being the infection of the surgical site the most frequent complication (2,362%), with 15 cases (5,906%) reoperated and 0.787% transferred to the ICU. CONCLUSION: The morbidity rate obtained was 65,667% and the mortality rate, 13,204%, in General Surgery patients according to the P-POSSUM system at the Hospital Belén de Trujillo.